Community-based learning collaboratives and participant reports of interprofessional collaboration, barriers to, and utilization of child trauma services. (November 2018) - Hanson, Rochelle F.; Saunders, Benjamin E.; Peer, Samuel O.; Ralston, Elizabeth; Moreland, Angela D.; Schoenwald, Sonja; Chapman, Jason
Abstract: Given the high prevalence and severe consequences of child trauma, effective implementation strategies are needed to increase the availability and utilization of evidence-based child trauma services. One promising strategy, the Community-Based Learning Collaborative (CBLC), augments traditional Learning Collaborative activities with a novel set of community-focused strategies. This prospective, observational study examined pre- to post-changes in CBLC participant reports of interprofessional collaboration (IPC), barriers to, and utilization of evidence-based child trauma treatment in their communities. Participants of five CBLCs from a statewide dissemination initiative, comprising 572 child abuse professionals (296 clinicians, 168 brokers, and 108 senior leaders), were surveyed pre- and post-CBLC participation. Results suggested that CBLCs significantly decreased barriers to child trauma treatment and significantly increased IPC and perceived utilization of evidence-based child trauma treatment. Further, changes in barriers partially mediated this relationship. Finally, small to medium differences in participants' reports were detected, such that senior leaders perceived significantly greater IPC than clinicians and brokers did, while brokers perceived significantly greater barriers to child trauma treatment than clinicians and senior leaders did. Collectively, these preliminary findings suggest the CBLC implementation model–which augments traditional Learning Collaborative models with a focus on fostering IPC–can reduce barriers and increase the utilization of evidence-based mental health treatment services. Highlights: Learning collaborative participation reduces barriers to child trauma services. Cross-discipline training fosters increased collaboration for child trauma services. Learning collaborative participation increases perceived use of trauma treatment. Perceptions of service barriers and collaboration varies by professional role.